Penetrating trauma to the neck: Using your vascular toolkit. Issue 2 (2nd August 2021) - Coleman, Kennith Conley; Hudnall, Aaron; Grabo, Daniel J.; Pillai, Lakshmikumar; Borgstrom, David C.; Wilson, Alison; Bardes, James M.
Abstract : Supplemental digital content is available in the text.